(3eONd Edi GdEbJUGO GdSjGSjs - (3YHO GddWja(B, (3Hf CTfghs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2007)
(3YQV GdeaghejI GdTcdGhjI,fbO GdWQM GdTcdGhj,GdeaghejI GdhGbYjI GdEbJUGOjI,eMGhdI cGQd HhdGJj,GdJGQjNjhf GdCdeGf,eaghejI ehQjS ahOhdjI,GdfbO GdYGe ddeaghejI,eaghe GdfXGe GdGbJUGOj,GdfXGe GdQCSeGdj,QCS GdeGd,aJQGJ QCS GdeGd,fThA GdQCSeGdjI,GdEjOjhdhLjI GdEbJUGOjI ddQCSeGdjI,GdYQV GdcjfRj dfXQjI GdEbJUGO Gdcdj ddJhGRfs
Keywords: (3GdGbJUGOs